Association between periodontitis and COVID-19 severity in a tertiary hospital: A retrospective cohort study - Nora Alnomay; Layan Alolayan; Raghad Aljohani; Razan Almashouf; Gharam Alharbi (Elsevier, 2022)
Introduction: Periodontitis is a chronic inflammatory disease caused by biofilm accumulation resulting in loss of periodontal attachment which could be linked to systemic implications. Coronavirus disease of 2019 (COVID-19) is a disease caused by SARS-CoV-2 that triggers damage to the lungs and other organs. COVID-19 and periodontitis share similar risk factors such as smoking, obesity, old age, and diabetes mellitus. Studies noted that periodontitis along with some systemic diseases has increased mortality. Thus, this study aims to examine the association of periodontitis with COVID-19 outcomes. Methods: This observational study included periodontitis group and non-periodontitis group for COVID-19 outcome assessment. Inclusion criteria were applied to select adults (≥18 years old) who showed at least one dental visit, and were isolated or admitted due to a COVID-19 complication (i.e. in-ward, ICU, or death). Exclusion criteria were patients with no active dental records. The periodontal status was examined from posterior bitewings and panoramic radiographs. The primary outcome assessed was COVID-19 complications versus no admission. Results and discussion: This study was the first of its kind as a retrospective cohort study to assess the association between periodontitis and COVID-19 severity in Riyadh, Saudi Arabia. Our findings revealed that periodontitis is statistically associated with COVID-19 severity. Periodontitis patients were three times more likely to have COVID-19 complications (p = 0.025). Diabetes (p = 0.004) and hypertension (p = 0.016) patients were 3.5 times more likely to have COVID-19 complications. Conclusion: Understanding the potential association between periodontitis and COVID-19 through systemic inflammation might be a pathway to achieve high quality medical care.